Conflict betwen Bankariya and other Stakeholders for the use of Forest Product - Gautam, Ramesh; Karki, Ram Bahadur (International Journal of Environment, 2014)
Socio-culturally and economically every rural community of Nepal are associated with forest for their livelihood and identity but simultaneously governmental policy for the protection of forest is not in the favor of people, which has been creating conflict between people and other stakeholder including governmental organization. This research tries to know the causes and consequences of conflict between Bankariya and other stakeholders. This research was carried out between the period May to December 2013. According to nature of the problem descriptive research design has been applied. Handikhola VDC of Makwanpur district has been selected as an universe purposively. Both primary and secondary sources of data were applied in this study. Case study, key informant interview and Focus Group Discussion (FGD) methods were applied for primary data collection. The findings shows that the living condition of Bankariya has changed after the government has provided them 6 hectors land for 40 years at Mushedhap. Still date forest based products are extremely beneficial for the enhancement of their livelihoods. The major problems faced by Bankariya community regarding to use of forest based resources are; not having their own permanent land for settlement and agriculture purpose, provision of present rules and regulation, and attitude of other elite persons/groups for dominating them. Forest resource based conflicts of Bankariya is mainly related with local people and other forest user group committee members as compared to Parsa Wild Life Reserve and District Forest Office of Makawanpur. DOI: http://dx.doi.org/10.3126/ije.v3i3.11080 International Journal of Environment Vol.3(3) 2014: 210-221